The kinetic theory of the cosmological models - Akhiezer, A.I.; Peletminsky, S.V. (Вопросы атомной науки и техники, 2001)
Theory of Friedman cosmological models is developed. It is based on a common and consistent solution of the kinetic equation for the galaxies distribution function in the approximation of a self-consistent gravitational field and the Einstein equations. Kinetic approach to the relic radiation theory is also under consideration.